Manusia pembina tamadun : perspektif pemikiran Islam - Zakaria Stapa (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Civilization is a product of the interactions between man and the enviroment. In this context, man is the main player in creating a civilization. From an Islamic perspective, man is provided by Allah with the necessary skills and attributes to carry out his role as a civilization builder. However, the quality of a civilization that is built is depending on the personal values of man himself. Therefore, the Islamic perspective posits that man, whose self-worth is based on his spirituality,must be trained so that he has a good moral standing, coupled with an unshakeable faith and consistently performing good deeds. And it is from these perso-nalities of man that the hope of a high quality civilization be build, which would subsequently ensure a high quality of life for all. This had been once concretely built by Muslims durings the Golden Era of the Islamic civilization.